Pancasila sebagai Solusi dalam Mengatasi Tantangan Sosial di Era Digital - Apriliani, Nayla; Debhyrizma Scevia Hardiyanti; Siti Nur Rizqia; Zalfa Aliyah Yusuf; Ratna Fitria (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study examines the application of Pancasila values as a solution to social challenges in the digital era 4.0. Using a descriptive qualitative method with a literature review approach, the research analyzes how Pancasila principles can be integrated into digital ethics to mitigate the negative impacts of digitalization. The digital era has significantly transformed communication and social interaction, yet it has also introduced challenges such as the spread of hoaxes, hate speech, and political polarization. The findings indicate that Pancasila values—such as unity, justice, and humanity—can serve as a strong foundation for digital ethics. Applying Pancasila in the digital context includes upholding ethical standards on social media, developing Pancasila-based digital policies, and preventing the misuse of technology. The study highlights the importance of collaboration among the government, educational institutions, and society in fostering an ethical digital culture. Recommended strategies include enhancing Pancasila-based digital literacy, establishing regulations that support digital ethics, and creating inclusive online spaces. In conclusion, Pancasila remains not only relevant as a state ideology but also as a practical solution to social challenges in the digital era, reinforcing social cohesion and national identity amid rapid technological advancements.